Reproductive Toxicity Of Endosulfan On Male Rats - BHARATH B.K,; CH. SRILATHA,; Y. ANJANEYULU, (International Journal of Pharma and Bio Sciences, 2011)
Endosulfan is an organochlorine insecticide extensively used to control pests of vegetables and fruits and is well absorbed by ingestion, inhalation and skin contact. Its toxicity, depends upon route of administration, vehicle and species and sex of animal. The present study was designed to evaluate the reproductive toxicity of sub chronic dose of endosulfan on male rats. Adult male rats were exposed to 0, 1.5, 3 and 6mg endosulfan /kg body weight through oral intubation for 45 days. Decreased testicular wet weight, reduced sperm count and increased sperm abnormalities associated with histopathological alterations like edema, degenerative changes, separation of epithelium from basement membrane, were observed in all the endosulfan treated rats in a dose dependent manner.